Illegitimacy in medieval Scotland, 1165-1500 - Marshall, Susan (Scottish historical review monograph second series, 2021)
Illegitimacy was an important subject in medieval Scotland. It was a legal barrier to inheritance, and its associations with wrongful sexual conduct could be socially stigmatising. We know that these disadvantages were taken seriously, since many parents turned to legal remedies either to ensure their children's legitimate status or to mitigate the effects of their illegitimacy. But neither legal sanctions nor the disapproval of illegitimacy that lay behind them extinguished the phenomenon of illegitimate birth in medieval Scottish society. Although we cannot know the full extent of its prevalence, there is plentiful evidence of it in royal and noble families and in the Scottish Church, and it was certainly known in urban life as well. Medieval Scots had a complex relationship with illegitimacy. Most understood it to be an undesirable condition linked to moral fault, but in general they accommodated this view alongside a pragmatic acceptance of their peers who were illegitimate or were parents of illegitimate offspring. The literary texts and chronicles examined in this study reveal something of these contemporary attitudes. They also provide some insight into how Scots, legitimate and illegitimate alike, engaged with illegitimacy to reconcile its negative associations with the reality that those born outside marriage may live as virtuously, and have as much to offer their communities, as anyone else. Consideration of the role of illegitimacy and illegitimates in political events and developments between 1165 and 1500 bears out the evidence of these texts, and reinforces the impression that Scottish people in the middle ages had a highly nuanced view of illegitimacy. Bringing together some of the many references to illegitimacy in medieval sources and examining them collectively provides compelling evidence that illegitimacy was more significant as a political, social and personal concern in medieval Scotland than has hitherto been recognised.